(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2022)
The number of adolescents who commit infractions is growing in Brazil, which makes the duty to act appear in the state, in order to repress such acts. It so happens that the current model of justice has been shown to be ineffective, since it does not re-educate the individual. The retributive system fails in its purpose, as its application disregards the rights of adolescents who commit infractions. This work aims to analyze the application of the restorative model to adolescents who practice infractions, and, based on this analysis, to verify how restorative techniques are used in the application of socio-educational measures. To achieve this, the bibliographic research method was used. Definitions about the restorative justice model and explanations of its techniques were found. There is little scientific production on the subject. In view of this, academic movement is necessary in order to bring the theme to the training spaces.